The RADEC Learning Model and its Effect on Understanding the Concept of Economic Activities of Grade IV Elementary School Students - Aam Sumia; Ahmad Mulyadiprana; Pidi Mohamad Setiadi (Journal of Practice Learning and Educational Development, 2025)
The goal of education is to develop learning processes that can help students reach their full potential through deliberate and planned efforts. Given the current state of the world, it is very important for elementary school students to understand the concept of economic activity. Students' conceptual understanding in various fields can be improved with the RADEC learning methodology. The purpose of this study is to determine how the RADEC (Read, Answer, Discuss, Explain, Create) learning model affects fourth-grade elementary school students' conceptual understanding of economic activities. A quantitative method using a quasi-experimental design with unequal control groups for pretest and posttest was employed. The experimental class, which received instruction using the RADEC learning model, and the control class, which received instruction using traditional methods, were the subjects of the study. Tests consisting of descriptive questions were administered before and after instruction as part of the data collection strategy. The Wilcoxon Signed-Rank test, Mann-Whitney U test, and N-Gain calculation were used to analyze the data. A significance level of less than 0.001 in the Wilcoxon test, along with the results of the Mann-Whitney test with an Asymp. Sig. 2-tailed < 0.001, indicate a significant improvement in conceptual understanding in the experimental class after the implementation of the RADEC learning model. In the less effective category, the average N-Gain of the experimental class was 46.06%, which was higher than the control class, which only achieved 21.28% and was classified as ineffective. Based on the results obtained, it can be concluded that the application of the RADEC model contributes to an increase in students' conceptual understanding, particularly in the field of Social Sciences related to economic activity topics.